2008 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--4196
|View full text |Cite
|
Sign up to set email alerts
|

Gearup: Teaching Engineering, Science, And Mathematics To Junior High And High School Students Through The Use Of K’nex Bridges

Abstract: Building Bridges to the Future is a GEAR UP program developed by mathematics, science, engineering, and education faculty from Louisiana Tech University. The primary goal of the project is to expose students from under-performing schools to mathematics, science, engineering, and literacy subject areas. Faculty members from the College of Engineering and Science have teamed up with the College of Education to develop engaging projects aimed at junior high and high school students. These projects utilize K'Nex b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…NASA-Threads provides school systems with a rigorous program that showcases a systems-level understanding of real-world applications of mathematics, science, and engineering. Our previous experience has shown that long-term impact on K12 students comes through close collaborative relationships between teachers and university faculty [4][5][6][7][8] . NASA-Threads provides a hands-on, context-based approach to math and science professional development in preparing teachers to become the educators of the future.…”
Section: Project Descriptionmentioning
confidence: 99%
“…NASA-Threads provides school systems with a rigorous program that showcases a systems-level understanding of real-world applications of mathematics, science, and engineering. Our previous experience has shown that long-term impact on K12 students comes through close collaborative relationships between teachers and university faculty [4][5][6][7][8] . NASA-Threads provides a hands-on, context-based approach to math and science professional development in preparing teachers to become the educators of the future.…”
Section: Project Descriptionmentioning
confidence: 99%